Response to "Mark Harris as a Naturalistic Theist" by Piotr Bylica - Harris , Mark (Filozoficzne Aspekty Genezy, 2023)
In this paper, I respond to a recent published analysis of my work by Dr Piotr Bylica, which characterises me as a “naturalistic theist”. I suggest that Bylica’s analysis takes this approach in order to fit my thought into his own “levels of analysis” scheme, but that it does not accurately represent my own theistic beliefs. I further argue that this process has resulted in the loss of important nuances in my work on areas such as miracles, dualism, and biblical interpretation.